Enhancing learning achievement and students’ satisfaction among the first year students of Zhoukou Normal University through problem-based learning - Li Xiaofeng; Lerlak Othakanon; Danucha Saleewong (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
The purposes of this research were to 1) compare learning achievements on Fundamentals of Information Technology course of the first year students at Zhoukou Normal University, China before and after using problem-based learning, 2) study learning achievements with an expectation of passing with the criteria 70 percent, and 3) study the student’s satisfaction towards problem-based learning organization. The samples were 66 students of the first year from Zhoukou Normal University and network engineering university which selected through cluster random sampling. The research instruments were: 1) the lesson plan 2) PBL pretest and posttest form, and 3) the satisfaction questionnaire. Data were analyzed by mean, standard deviation, and t-test. The findings revealed that: 1) post-learning of students was higher than their pre-learning with statistical significance at the level .05. 2) The learning achievement of students was 89 percent that higher than the standard criteria of 70 percent with statistical significance at the level .05. 3) The students’ satisfaction after learning was at a highest level.